Pain and pessimism affect calves' play behaviours post-disbudding - Amelia St John Wallis; Suzanne D. E. Held; Michael T. Mendl; Marina A. G. von Keyserlingk; Daniel M. Weary; Benjamin Lecorps (Discover Animals)
Abstract Calves are expected to play less when in pain, and more pessimistic individuals may be more affected by painful events, such as hot-iron disbudding (i.e., horn-bud removal). We explored 1) the impact of disbudding on different play behaviours, predicting that those involving the head (e.g., play-fighting) may be more sensitive to disbudding due to the injury location, and 2) the effect of ‘pessimism’ (assessed using the judgement bias test) on changes in play post-disbudding. Holstein female calves (n = 19) were housed in groups of 10, individually tested for judgement bias at 25 days old, and disbudded following the farm’s standards (including sedation and local anaesthesia) at 45 days old. Individual and parallel locomotor play and play-fighting were recorded for 4 h/day (from 1800 to 2200 h) for 5 days before disbudding, on disbudding day, and for 7 days after. Play-fighting reduced after disbudding compared to baseline and did not recover over 7 days. Locomotor play did not change on disbudding day and increased on the day after compared to baseline. More pessimistic calves did not show greater changes in play post-disbudding, but they showed a smaller increase in locomotor play on the day after disbudding, suggesting they did not recover as well as the others. Overall, play-fighting (i.e., pushing with the head) may be a more sensitive indicator of disbudding pain than other play behaviours, likely reflecting calves avoiding evoked pain, which may persist for at least 7 days. Our results also add to the growing literature demonstrating that pessimistic expectations affect animals’ ability to cope with stressors.